Encyclopedia of Life Sciences 2016
DOI: 10.1002/9780470015902.a0020094.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Plant Disease Resistance

Abstract: Disease is a major agent of evolution by natural selection because infection by a parasite reduces the fitness of its host. Plant populations have evolved many different mechanisms of resistance in response to disease, but, curiously, resistant genotypes rarely supplant susceptible genotypes. Instead, many plant populations are polymorphic at resistance gene loci, meaning that both resistant and susceptible genotypes coexist within a population. The maintenance of polymorphism can be explained if host resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Also, if there is a difference between parents and nonparents, one should test whether this effect can be attributed to pathogens (as most previous results did not identify the source of mortality). Finally, we are not aware of any study showing a cost of R-genes in species other than Arabidopsis thaliana (Bruns 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Also, if there is a difference between parents and nonparents, one should test whether this effect can be attributed to pathogens (as most previous results did not identify the source of mortality). Finally, we are not aware of any study showing a cost of R-genes in species other than Arabidopsis thaliana (Bruns 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Yet the nature of age-specific immunity varies widely, with adults better protected than juveniles in many [5][6][7][8][9][10][12][13][14][15][16][17] but not all cases [4,11,12,18]. Differences in age-related patterns of host immunity exist both within and between species [19][20][21][22], but the reasons behind these diverse patterns are not always well understood. In particular, we lack a detailed understanding of the factors affecting differences in selection for host defences against infectious disease at different host life stages.…”
Section: Introductionmentioning
confidence: 99%
“…Trivially, physiological constraints may constrain juvenile defences in some species, preventing juveniles from evolving stronger protection against parasitism or herbivory [33,34]. Although this may provide a partial explanation for supressed juvenile defences, artificial selection for increased innate immunity [35][36][37] and evidence of polymorphism in the level of immunity in natural populations [19][20][21][22][38][39][40] have shown that many hosts do not possess the maximum possible level of juvenile immunity. Hence physiological constraints on juvenile defences do not provide a full explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Trivially, physiological constraints may constrain juvenile defences in some species, preventing juveniles from evolving stronger protection against parasitism or herbivory [33,34]. Although this may provide a partial explanation for supressed juvenile defences, artificial selection for increased innate immunity [35][36][37] and evidence of polymorphism in the level of immunity in natural populations [19][20][21][22][38][39][40] have shown that many hosts do not possess the maximum possible level of juvenile immunity. Hence physiological constraints on juvenile defences do not provide a full explanation.…”
Section: Introductionmentioning
confidence: 99%